The Role of Mandibular Third Molars on Lower Anterior Teeth Crowding and Relapse after Orthodontic Treatment: A Systematic Review - Khalid H. Zawawi; Marcello Melis (The Scientific World Journal)
Aims. To evaluate the role of third molars in the development of crowding or relapse after orthodontic treatment in the anterior segment of the dental arch. Methods. PubMed search of the literature was performed selecting all the articles relevant to the topic and limiting the studies to controlled trials on humans and written in English language. Systematic review was conducted according to the PRISMA (preferred reporting items for systematic reviews and meta-analyses) statement. Results. A total of 12 clinical studies were included in the review. A high risk of bias was found in most of the articles, either because the relative items assessed were inadequate or because they were unclearly described. The third molars were not correlated with more severe anterior tooth crowding in most of the studies. However, four of them described a different outcome. Conclusion. Definitive conclusions on the role of the third molars in the development of anterior tooth crowding cannot be drawn. A high risk of bias was found in most of the trials, and the outcomes were not consistent. However, most of the studies do not support a cause-and-effect relationship; therefore, third molar extraction to prevent anterior tooth crowding or postorthodontic relapse is not justified.